2018
DOI: 10.1016/j.anbehav.2018.04.018
|View full text |Cite
|
Sign up to set email alerts
|

Which male and female characteristics influence the probability of extragroup paternities in rhesus macaques, Macaca mulatta?

Abstract: Extragroup paternity (EGP) is found across a wide range of species and may entail reproductive benefits, but may also entail costs to both sexes. While population and group parameters affecting the degree of EGPs are relatively well established, less is known about the individual characteristics that make males and females engage in alternative reproductive tactics such as EGP. Applying a combination of long-term demographic and genetic data from the rhesus macaque population of Cayo Santiago (Puerto Rico, U.S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 72 publications
0
1
0
Order By: Relevance
“…While some studies have found a positive effect of pair relatedness on EPP (e.g., Blomqvist et al 2002; Cohas et al 2006; Freeman-Gallant et al 2006; Leclaire et al 2013), others have shown no effect (e.g., Schmoll et al 2005; Edly-Wright et al 2007; Barati et al 2018). Mixed evidence has resulted also from meta-analyses (in favor: Arct et al 2015; against: Ackay and Roughgarden 2007) and from research on polygynandrous species, which addressed the effect of female–male relatedness (within a group) on EGP levels (e.g., Nichols et al 2015 versus Ruiz-Lambides et al 2018). In the Seychelles warbler, we only detected a positive relationship between genetic relatedness and EGP likelihood for subordinate mothers.…”
Section: Discussionmentioning
confidence: 99%
“…While some studies have found a positive effect of pair relatedness on EPP (e.g., Blomqvist et al 2002; Cohas et al 2006; Freeman-Gallant et al 2006; Leclaire et al 2013), others have shown no effect (e.g., Schmoll et al 2005; Edly-Wright et al 2007; Barati et al 2018). Mixed evidence has resulted also from meta-analyses (in favor: Arct et al 2015; against: Ackay and Roughgarden 2007) and from research on polygynandrous species, which addressed the effect of female–male relatedness (within a group) on EGP levels (e.g., Nichols et al 2015 versus Ruiz-Lambides et al 2018). In the Seychelles warbler, we only detected a positive relationship between genetic relatedness and EGP likelihood for subordinate mothers.…”
Section: Discussionmentioning
confidence: 99%